Paper making potential of Acacia dealbata and Acacia melanoxylon - Santos, A. (2019)
Submitted by Ofélia Anjos (ofelia@ipcb.pt) on 2019-03-21T22:41:39Z No. of bitstreams: 1 2006_Papermaking potential of Acacia dealbata and Acacia melanoxylon.pdf: 160881 bytes, checksum: 4792e45ed6151dd4ecb3096a68ab42c0 (MD5)